2021
DOI: 10.1016/j.cgh.2019.12.016
|View full text |Cite
|
Sign up to set email alerts
|

What Multilevel Interventions Do We Need to Increase the Colorectal Cancer Screening Rate to 80%?

Abstract: Screening reduces colorectal cancer mortality; however, this remains the second leading cause of cancer deaths in the United States and adherence to colorectal cancer screening falls far short of the National Colorectal Cancer Roundtable goal of 80%. Numerous studies have examined the effectiveness of interventions to increase colorectal cancer screening uptake. Outreach is the active dissemination of screening outside of the primary care setting, such as mailing fecal blood tests to individuals' homes. Naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
(66 reference statements)
0
23
0
3
Order By: Relevance
“…To improve CRC screening through initial and follow-up colonoscopy completion, multi-component interventions are needed (34). Our prior work and other published research have identified multiple barriers and facilitators to colonoscopy completion at the patient, provider, and health-system level for which there are practical solutions (17,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…To improve CRC screening through initial and follow-up colonoscopy completion, multi-component interventions are needed (34). Our prior work and other published research have identified multiple barriers and facilitators to colonoscopy completion at the patient, provider, and health-system level for which there are practical solutions (17,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance with a second colonoscopy screening in low-risk individuals could be replaced by surveillance with the more affordable screening method using a quantitative fecal immunochemical blood test (FIT) every one to two years. Evidence indicates that the use of FIT at screening has better acceptance and detects many cancers early 16 20 48 49 50 51 . The stool test should at least be offered to low-risk individuals as an additional choice for colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Leider wird aber nicht selten nicht einmal jeder zweite positive FIT abgeklärt [18,19]. Viele Personen haben den Sinn von FIT nicht richtig verstanden oder fürchten sich vor der Endoskopie und deren Resultat [20,21]. Würde bei der Mitteilung des Testresultats gleich ein im Voraus fixierter Termin für die Koloskopie angeboten, könnte die Abklärungsrate wesentlich verbessert werden [22][23][24], wie dies bei der Mammographie, beim Zervixabstrich und der Sigmoidoskopie gezeigt wurde.…”
Section: Was Nützt Das Testangebot?unclassified